2010
DOI: 10.1002/term.248
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of fibronectin in chitosan substrates improves cell adhesion and proliferation

Abstract: Covalent grafting of biomolecules is a strategy to improve the biocompatibility and bioactivity of materials. However, it is critical to maintain the biological activity of the biomolecule upon its attachment to the surface. In the present study we compared the biological properties of chitosan, in which the surface was enriched with fibronectin (Fn), using two methodologies: chemical immobilization, using a water-soluble carbodiimide; and simple adsorption. X-ray photoelectron spectroscopy studies confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 35 publications
(39 reference statements)
2
51
0
Order By: Relevance
“…The release rate in lysozyme was much faster, which should be attributed to the degradation caused by lysozyme. 26 Although many reports hold the idea that chitosan film could improve cell adhesion and proliferation, 16,27 there are also conflicts that there is no significant cell growth improvement. 26,28 Our result is in agreement with the latter that no significant difference of attachment and viability has been observed between CS-MAO and MAO, and because Sema3A has no dramatic influence on cellular viability and proliferation, 13 CS/Sema-MAO has not shown enhancement of cell growth either.…”
Section: Discussionmentioning
confidence: 99%
“…The release rate in lysozyme was much faster, which should be attributed to the degradation caused by lysozyme. 26 Although many reports hold the idea that chitosan film could improve cell adhesion and proliferation, 16,27 there are also conflicts that there is no significant cell growth improvement. 26,28 Our result is in agreement with the latter that no significant difference of attachment and viability has been observed between CS-MAO and MAO, and because Sema3A has no dramatic influence on cellular viability and proliferation, 13 CS/Sema-MAO has not shown enhancement of cell growth either.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that increased cell proliferation with increasing FN grafting is consistent with the findings of a recently published work on natural carbohydrate polymers grafted with FN. 33 Although the assay results revealed that both Fbg and FN/Fbg were biocompatible, the microfibers containing nanostructures could enhance much higher cell proliferation compared to highly porous and less porous microfibers. It is well known that FN is a large ECM protein that has been extensively studied because of its significant role in numerous physiological processes, such as cell adhesion, migration, proliferation, survival, and wound healing.…”
Section: Cell-viability Studymentioning
confidence: 95%
“…32,33 Briefly, with some modification, Fbg microfibers were covalently cross-linked with FN, using EDC as a cross-linking agent. The cross-linking reaction consisted of two steps.…”
Section: Covalent Cross-linking Of Fn or Fn Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Published works report the coating or tailoring of biomaterials with bioactive molecules, such as fibronectin [3], laminin [4], growth factors [5,6] or their integrin-binding epitopes including RGD [7,8] and GFOGER [9]. These studies report the influence of such biomolecules in cell adhesion, differentiation or proliferation.…”
Section: Introductionmentioning
confidence: 99%